ACCOUNTING TREATMENT OF PROFIT AS SHARING PROFIT IN MUSYARAKAH TERM AMONG MEMBERS - Hamdi, Muhammad Nurul (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2015)
AbstractEach member of shariah cooperative are same as a partner and having the same rights and obligations.This condition is internalized by policy in all activities and business operations. Especially the profit will be distributed to members. It’s meant to see how the cooperatives shariah of ahmad yani manages the difference between the results of their business. The research has descriptived qualitative research that aimed at giving information about the method of calculation and recording as for the result of accounting report of SHU or income in the end of year musyarakah among members in cooperatives shariah of ahmad yani unfortunate.The analysis uses instrument of the descriptive analysis that gives a technical and mathematical formula that the calculation can be compared with the shariah principle and cooperative regulation applicable. Based on the research, it was known that the SHU methods and distribution is in accordance with the rule of Indonesia cooperative No. 25 1992, but accounting methods that related to the profit which will be distributed to members of the cooperative is not suitable with act no. 8 DSN-MUI. The MUI explanation about musyarakah which SHU is about the activities are still measured from savings and not accommodate from the capital and other business activities.Meanwhile, by this condition that cooperative shariah still need developing of the accountance and good recording.AbstrakDalam koperasi syariah setiap anggota berkedudukan sebagai mitra yang berserikat dan memiliki hak serta kewajiban yang sama. Kondisi ini diinternalisasikan dalam kebijakan dan segala aktivitas operasi usahanya. Terutama perlakuan laba atau SHU yang akan dibagikan kepada anggota. Hal ini yang ingin dilihat bagaimana Koperasi Serba Usaha Syariah Ahmad Yani mengelola Selisih Hasil Usahanya (SHU).Penelitian ini merupakan penelitian kualitatif deskriptif yang bertujuan untuk memberikan informasi tentang metode perhitungan dan pencatatan akuntansi SHU sebagai bagi hasil dari musyarakah antar anggota di Koperasi Serba Usaha Syariah Ahmad Yani Malang. Alat analisis yang digunakan adalah analisis deskriptif yaitu untuk memberikan gambaran rumusan matematis dan teknis perhitungannya sehingga dapat dibandingkan dengan prinsip syariah dan aturan perkoperasian yang berlaku. Berdasarkan penelitian, diketahui bahwa dari metode perhitungan total SHU dan pendistribusian SHU kepada pos-pos tertentu sudah sesuai dengan UU. No. 25 Tahun 1992 tentang Perkoperasian. Namun untuk metode perhitungan alokasi SHU yang akan dibagikan kepada anggota belum sesuai dengan UU Perkoperasian dan Fatwa DSN-MUI No. 8 tentang Musyarakah di mana SHU yang diterima anggota masih diukur dari aktivitas tabungan saja dan belum mengakomodir kontribusi modal dan aktivitas usaha lainnya. Sementara untuk pencatatan akuntansinya masih perlu pengembangan di beberapa pencatatan.